Aplicación de una auditoría financiera para medir la razonabilidad de los estados financieros en la asociación de productores agropecuarios “Pucayacu” en la provincia de Cotopaxi, cantón La Maná, año 2012 - Sigcha Patango, Cecilia Carolina (2014)
This investigation was developed in “PUCAYACU” Farmers Association, located in La Maná Canton, Cotopaxi Province, the main objective was to apply a Financial Audit to measure the financial statements reasonableness in 2012, the used theoretical methods to collect the information were the interview, and the survey and the audit methodology through which the significant results about the situation of the association were got. The applied financial audit constitutes a systematic exam and support instrument for associates and administrative staff in the efficient and effective management of their activities.